A nano-polycrystalline diamond anvil cell with bulk metallic glass cylinder for single-crystal neutron diffraction. Issue 1 (2nd January 2020) - Yamashita, Keishiro; Komatsu, Kazuki; Klotz, Stefan; Fernández-Díaz, Maria T.; Fabelo, Oscar; Irifune, Tetsuo; Sugiyama, Kazumasa; Kawamata, Tooru; Kagi, Hiroyuki
ABSTRACT: A high-pressure cell for in-situ single-crystal neutron diffraction was developed. The cell uses nano-polycrystalline diamond anvils in a tubular load frame made of bulk metallic glass which is highly transparent to neutrons and does not produce Bragg reflections. Diffraction peaks from a sample can be measured from almost any direction and the simple geometry of the cell allows accurate attenuation corrections. We demonstrate the operation of the cell by ambient-pressure experiment using a single-crystal of NaCl on the D9 diffractometer at the Institute-Laue-Langevin. A high-pressure experiment was also carried out on a single crystal of ice VII at 2.35 GPa showing the potential to detect weak diffraction spots. The correct integration of weak reflections together with the simple attenuation correction will help to carry out precise structure analysis and address new scientific problems using neutron diffraction.